Epimedium muhuangense (Berberidaceae), a new species from China - Wang, Yue-Yun; Xu, Wen-Fen; He, Shun-Zhi (Phytotaxa, 2017)
Epimedium muhuangense (Berberidaceae), a new species from Guizhou, China, is described and illustrated. This species is most closely similar to E. elachyphyllum in having simple leaves, petals shorter than inner sepals, flowers less than 10 mm in diameter and in having the same pollen morphology as well, but differs by having stout, short rhizomes, two opposite, glabrous leaves on flowering stems, and paniculate inflorescences. The chromosomes of E. muhuangense is counted as 2n = 12 and the karyotype is formulated as s 2n = 2x = 6m (2sat) + 6sm. Line illustrations, color photographs, and micrographs of chromosomes and of pollen grains of E. muhuangense are provided.